Utilization of hydrophilic cellulose fibers for preparation of plaster with enhanced moisture control capability. (June 2019) - Fort, J; Kocí, J; Vejmelkova, E; Dolozelova, M; Cerny, R
Abstract: The relative humidity is one of the most important parameters having a substantial impact on ambient climate comfort. The negative effects induced by undesired levels of relative humidity in building interiors are related not only to a deterioration of materials but also to a potential health risk for building occupants. In the recent paper, a traditional lime plaster is modified by biomass fly ash and hydrophilic cellulose fiber admixture to improve material durability and provide material with enhanced capability for the moderation of ambient relative humidity. Within the experimental analysis, the basic material properties, as well as mechanical strength of designed plaster, is determined. The moisture buffer potential of all designed plasters is evaluated according to the Nordtest test procedure. Obtained results show that the application of cellulose fibers has a synergic effect on both improvements of the potential of studied plaster for passive adjustment of interior relative humidity and mechanical strength.